Association of IL23R and ATG16L1 with susceptibility of Crohn's disease in Chinese population - Zhang, Jie; Chen, Jiebin; Gu, Jianjun; Guo, Huimin; Chen, Weichang (Scandinavian journal of gastroenterology, 2014)
To investigate whether gene polymorphisms of ATG16L1 and IL23R are associated with the susceptibility of Crohn's disease (CD) in Chinese population. A total of 420 patients with CD and 450 age- and sex-matched healthy volunteers from Chinese Han population were included in this study. Single nucleotide polymorphisms (SNPs) rs2241880 of ATG16L1 and rs11209026, rs1004819, and rs1495965 of IL23R were genotyped. The differences of genotype and allele distributions between CD patients and healthy controls were assessed using the Chi-squared test. Besides, subgroup analysis of disease groups was performed using the Chi-squared test. For ATG16L1, patients were found to have significantly higher proportion of genotype GG (18.3%), when compared with the normal controls (12.4%). Allele G was found to be the risk allele for the disease (34.3% vs. 29.0%, p = 0.016) with an odds ratio of 1.18. For IL23R, all three SNPs were found not to be associated with the development of CD. None of these four SNPs was found to be associated with the clinical features of the patients, including age at diagnosis, disease location, and behavior. The original genome-wide association studies finding on ATG16L1 gene should be robust and this gene does play a role in the pathogenesis of CD in the Chinese population. However, the role of IL23R gene in the occurrence of CD remains obscure.